Image Compression Techniques - Singh Samra, Hardeep (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Digital images required large number of bits to represent them and in their canonical representation, generally contain significant amount of redundancy. Image compression techniques reduce the number of bits required to represent an image by taking advantage of these redundancies.To overcome this redundancy several image compression techniques are discussed in this paper along with their benefits.